Pemberdayaan Perempuan dalam Pemanfaatan Limbah Kulit Kerang Menjadi Keterampilan Keluarga di Kabupaten Batu Bara - Sudirman Sudirman; Rusmawati Rusmawati; Rosramadhana Rosramadhana (Universitas Negeri Medan, 2022)
Seashells are still a waste for some people in Batu Bara Regency, which can still be used as a skill for housewives so that they have economic value. The purpose of this research is to find out the results of women's empowerment in utilizing leather waste in family skills. This type of research is an experiment in the form of a Posttest Only Control Design. The sample size for this research is 30 housewives in Medang Village, Medang Deras District, Baatu Bara Regency. The data collection technique was carried out by structured observation and descriptive data analysis and tested using the t test. The results of the data analysis showed that the average value in the control class was 5.2, with the highest score of 7 and the lowest score of 3. While the average value of the experimental class was 9.53, with the highest score of 12 and the lowest score of 8. It can be concluded that empowerment activities for women in the experimental class are better than those in the control class. From the results of hypothesis testing, it was obtained that t count > from the t table, namely 12,964 > 1,771 at a level of = 0.05. Thus, the implementation of women's empowerment in the utilization of shell waste has an influence on family skills.